Perancangan Game RPG untuk Pembelajaran Bahasa Inggris dengan Metode ADDIE - Tony Wibowo; Felnando Xie (Universitas Sarjanawiyata Tamansiswa, 2022)
Technology makes easier to study English language easier by social media, websites, books, or even seminars. RPG game is a type of game that tell the story and information by virtual and interactive path. Most students that struggling learning English have faced complexity and difficulty in learning them. This study aims to create a RPG game that can help learning English. The method used for this study is ADDIE (Analysis, Design, Development, Implement, Evaluate) method and the software required for this study are Unity and Visual Studio 2019. ADDIE method is a learning model that instructional designers and training developers have used to create methods of learning effectiveness learning, this learning model is an acronym for a five-step process which are: Analysis, Design, Development, Implementation, and evaluation. And therefore the software used to develop the game are Unity. The result of this research is a RPG game that can be used for learning English. With this RPG game, it is hoped that the game can help with students who struggle learning English.